Green Finance and Its Role in Promoting Sustainable Development - Julia Simmons (Universal Research Reports, 2019)
The study explores the role of green finance in promoting sustainable development, focusing on green bonds, climate finance, and impact investment. The research examines how financial institutions can support sustainability initiatives by offering incentives for projects that reduce carbon emissions and promote renewable energy. The findings suggest that green finance is critical for bridging the gap between sustainability goals and economic growth.